2011
DOI: 10.1016/j.enbuild.2011.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Meeting residential ventilation standards through dynamic control of ventilation systems

Abstract: Existing ventilation standards, including American Society of Heating, Refrigerating, and Air-conditioning Engineers (ASHRAE) Standard 62.2, specify continuous operation of a defined mechanical ventilation system to provide minimum ventilation, with time-based intermittent operation as an option. This requirement ignores several factors and concerns including: other equipment such as household exhaust fans that might incidentally provide ventilation, negative impacts of ventilation when outdoor pollutant level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…The larger value for lim R allows the ventilation device to be off for longer periods while the house is unoccupied, as the inhabitants will not be exposed to the higher levels of indoor contaminants, while limiting the peak levels that a returning occupant is exposed to at the beginning of the occupancy period. Previous work by Sherman and Walker (2011) has shown that a fan sized to 125% of the ASHRAE 62.2 minimum ventilation rate is required for a fan that will be switched off for at least four hours every day (the peak energy demand period).…”
Section: Rivec Control Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…The larger value for lim R allows the ventilation device to be off for longer periods while the house is unoccupied, as the inhabitants will not be exposed to the higher levels of indoor contaminants, while limiting the peak levels that a returning occupant is exposed to at the beginning of the occupancy period. Previous work by Sherman and Walker (2011) has shown that a fan sized to 125% of the ASHRAE 62.2 minimum ventilation rate is required for a fan that will be switched off for at least four hours every day (the peak energy demand period).…”
Section: Rivec Control Algorithmmentioning
confidence: 99%
“…The controller does this by shifting the ventilation load of the whole-house mechanical ventilation system off-peak and taking into account auxiliary mechanical ventilation by other systems (Sherman and Walker, 2011). Other ventilation controllers are available, but unlike RIVEC they do not i) account for the contributions of other systems that mechanically ventilate a home, ii) have the ability to avoid times of peak energy and monetary ventilation cost, or iii) have the capability to track IAQ levels only during occupied hours.…”
Section: The Residential Integrated Ventilation Controller (Rivec)mentioning
confidence: 99%
See 3 more Smart Citations